SIFAT PEMESINAN 10 JENIS KAYU DARI DAERAH NUSA TENGGARA BARAT - Osly Rachman; Sri Rulliaty (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
Machining properties of ten wood species from West Nusa Tenggara is reported in this paper.The sample material was tested under ASTM D-1666 that was modified according to Forest Products Research Institute Report No.160 (1982). The samples (25 pieces/species) were dried to equilibrium moisture content condition (15 to18 % of MC). The machining properties tested are planing, shaping, boring, turning, and sanding.Four species that have good to very good machining properties are Anthocephalus cadamba Miq., Duabanga moluccana BL., Eugenia longiflora (Presl.) F. Viii., and Eugenia polyantha Wight. Whereas the other species have poor machining properties i.e., Ailanthus malabarica DC, Ficus microcarpa L.f and Palaquium javense Burck.